Methodological comparison of bronchoalveolar lavage fluid-based detection of respiratory pathogens in diagnosis of bacterium/fungus-associated pneumonia in critically ill patients - Zhang, Luwen; Lu, Fanbo; Wang, Yuerong; Ji, Juanjuan; Xu, Yuanhong; Huang, Ying; Zhang, Min; Li, Moyan; Xia, Jinxing; Wang, Bo (Frontiers in Public Health, 2023)
Background: Bacterium/fungus-associated pneumonia (BAP/FAP) is the prominent cause of high mortality and morbidity with important clinical impacts globally. Effective diagnostic methods and proper specimen types hopefully facilitate early diagnosis of pneumonia and prevent spread of drug-resistant bacteria/fungi among critically ill patients. Methods: In the present study, 342 bronchoalveolar lavage fluid (BALF) samples were collected from critically ill patients with pulmonary infections between November 2020 and March 2021. The BALF materials were comparatively employed to screen BAP/FAP through microscopy, culture, antigenic marker and PCR-based methods. The limit of detection (LOD) of cultures and PCR for bacteria/fungi was determined by serial dilution assays. Specimen slides were prepared with Gram staining for microscopic examinations. Microbial cultures and identifications underwent routine clinical protocols with the aid of mass spectrometry. (1,3)-β-D-glucan and galactomannan tests with BALF were carried out accordingly. Direct detection of pathogens in BALF was achieved through PCR, followed by sequencing and BLAST in GenBank database for pathogenic identification. The subjects’ demographic and clinical characteristics were well evaluated. Results: BAP/FAP was identified in approximately 47% of the subjects by the BALF-based PCR. The PCR-based diagnostic methods showed improved detection performance for fungi with good LOD, but performed similarly for bacteria, when compared to the cultures. There was poor agreement among traditional microscopy, culture and PCR assays for bacterial detections (kappa value, 0.184 to 0.277). For overall bacterial/fungal detections, the microscopy showed the lowest detecting rate, followed by the cultures, which displayed a slightly higher sensitivity than the microscopy did. The sensitivity of PCR was much higher than that of the other means of interest. However, the traditional cultures rather than antigenic marker-based approaches were moderately consistent with the PCR-based methods in fungal species identification, particularly for Candida and Aspergillus spp. Our findings further revealed that the age, length of hospital stay, invasive procedures and cerebral diseases were likely considered as main risk factors for BAP/FAP. Conclusion: Screening for BALF in critically ill patients with suspected pneumonia pertaining high risk factors using combined PCR-based molecular detection strategies would hopefully contribute to early diagnosis of BAP/FAP and improved prognosis of the patients.